(untitled) (Práxis Educativa, 2023)
This article introduces the internationalisation and interculturality from Neohumanist perspective. Neohumanism was propounded by the great Indian philosopher Prabhat Ranjan Sarkar (1921-1990). As a key approach to internationalisation, Sarkar emphasised manifestation of human qualities that lie in the subtle layers of mind. Humanism newly explained and newly-sermonized is Neohumanism – the philosophy which will make people understand that they are not merely ordinary creatures. This philosophy will liberate them from all inferiority feelings and defects and make them aware of their own importance it will inspire them to build a new world. All beings – animate and inanimate - come within the scope of Neohumanism which will eliminate all sentiments like geo-sentiment, socio-sentiment and will usher in universalism. Implementation of principles of Progressive Utilization Theory (PROUT) in economic sphere will provide guaranteed provision of basic amenities of life like food, clothing, shelter, education and medical treatment to all segments of the society. Neohumanist education focuses on instilling universal moral values among the students. Keywords: Neohumanism. Progressive Utilization Theory. Internationalization. Interculturality.